rac-4,5-trans-Dibromo-9,9-dichloro-cis-bicyclo[6.1.0]nonane - Heiner Detert; Dieter Schollmeyer (IUCrData)
The crystal structure of the title tetrahalogenated bicyclononane, C9H12Br2Cl2, is reported. The molecule adopts a distorted twist-chair conformation. The cyclopropane ring is almost parallel to the plane formed by the four methylene carbon atoms.